Cognition and the Web: Moving from Theory to Web Design - Czerwinski, Mary; Larson, Kevin (Human Factors and Web Development, 2002)
The links from basic cognitive theory to applied web design practice are not as strong as we would like to see. This chapter outlines some areas in which the two disciplines complement each other. We also describe several challenges such as designing websites from first principles and moving both fields forward in mutually beneficial ways. Although much progress has been made in the last few years, we believe that both disciplines can benefit from a closer partnership, and we hope that this chapter begins to detail some inspiration for that advancement. We will discuss many examples from our own research and identify when designing from first principles was successful, as well as when more work was needed to complete a good web design. We would like to encourage people performing basic research to use more challenging real-world tasks like web navigation and web search for their scientific inquiries. In addition, it is clear that theory and practice from many other disciplines are needed to bridge the gap, including the fields of computer science, anthropology, information visualization and design.